Manajemen dan Kebijakan Madrasah melalui Penguatan Tata Kelola, Akuntabilitas dan Citra Publik Pendidikan - Hikmah, Afroh Nailil; Yudiawan, Agus (Tarbiyah STAIN Sorong, 2019)
Strengthening governance, accountability, and public image is a work of the national education plan. This policy aims to improve the capacity and competency management and budgeting of education in the implementation and management to realize transparent and accountable education so as to create the image and services of the school/madrasah quality sound and accountable manner. These objectives can be achieved through, autonomy and decentralization of education, school-based management/madrasah, community-based management, and image enhancement.